2014
DOI: 10.1007/s13197-014-1615-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of novel bactericidal Cu/HPMC BNCs using chemical reduction method for food packaging

Abstract: In this research copper nanoparticles (Cu NPs) were incorporated in the biodegradable hydroxypropyl methylcellulose (HPMC) matrix using the simple and low cost chemical reduction method for application as food packaging material. The properties of Cu/HPMC bionanocomposites (BNCs) were studied as a function of the CuSO 4 concentration. Surface morphology of the film was investigated by scanning electron microscopy. Mechanical analysis and water vapor barrier properties of HPMC/Cu nanocomposites were analyzed. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 25 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…The fish were incubated between 28±2°C/examined daily for 7, 14, and 18 days and 18±2°C/examined daily for 18 days. The experiments were repeated at least 5 times using each concentration for results confirmation (Ebrahimiasl and Rajabpour, 2015;Al-Naamani et al, 2016).…”
Section: Determination Of the Storage Period Of Fish Using Packages C...mentioning
confidence: 99%
“…The fish were incubated between 28±2°C/examined daily for 7, 14, and 18 days and 18±2°C/examined daily for 18 days. The experiments were repeated at least 5 times using each concentration for results confirmation (Ebrahimiasl and Rajabpour, 2015;Al-Naamani et al, 2016).…”
Section: Determination Of the Storage Period Of Fish Using Packages C...mentioning
confidence: 99%
“…This film was prepared by mixing pre-synthesized CuNPs using a microwave assisted method with the LDPE polymer solution. In another study, a CuNPs-HPMC binary film showed potential for food packaging due to the increased antimicrobial activity, gas barrier properties, and the inhibition of the total bacteria count in a packed sample of minced meat (Table 1) (Ebrahimiasl & Rajabpour, 2015).…”
Section: Binary Polymer-metallic Compositesmentioning
confidence: 99%
“…The obtained articles were selected based on the following eligibility criteria according to our search strategy (Figure 1): (1) only articles published in the recent 10 years were considered; (2) only English articles were selected (studies in other languages were excluded); (3) only original research articles were chosen (review articles were removed); (4) only full text and peer-reviewed journal articles were considered; (5) only research articles directly associated with NPs for food packaging were selected. In the end, 19 articles were included in the literature review part of this study [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Study Selectionmentioning
confidence: 99%